Refractive indices and density of cryovacuum-deposited thin films of methane in the vicinity of the α–β-transition temperature - Drobyshev, A.; Aldiyarov, A.; Sokolov, D.; Shinbayeva, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Experimental studies of the effect of methane condensation temperature on the value of the refractive index and density of the resulting thin films are reported. The main unit of the installation is a high-vacuum chamber, which routinely operates at 10–8–10–6 Torr. Measurements using a two-beam He–Ne laser interferometer in thevicinity of the methane phase transition temperature T = 20.4 K in the range of 14–32 K were carried out. It has been shown that in the vicinity of T = 20 K the temperature dependence of the refractive index undergoes an abrupt decrease with decreasing temperature. It is assumed that this gap is the result of the phase transition from the orientational disordered phase (α-phase) to the partially ordered phase (β-phase) of solid methane. The calculations of the polarizability of the methane molecules in the solid phase at two values of the deposition temperature T = 16 K and T = 30 K were performed using the Lorentz–Lorenz equation.